Medical, welfare, and educational challenges and psychological distress in parents caring for an individual with 22q11.2 deletion syndrome: A cross‐sectional survey in Japan. Issue 1 (3rd September 2021) - Morishima, Ryo; Kumakura, Yousuke; Usami, Satoshi; Kanehara, Akiko; Tanaka, Miho; Okochi, Noriko; Nakajima, Naomi; Hamada, Junko; Ogawa, Tomoko; Ando, Shuntaro; Tamune, Hidetaka; Nakahara, Mutsumi; et al.
Abstract: Parents of children with 22q11.2 deletion syndrome (22q11DS) experience distress not only due to multimorbidity in the patients, but also due to professionals' lack of understanding about 22q11DS and insufficient support systems. This study investigated relationships between medical, welfare, and educational challenges and parental psychological distress. A cross‐sectional survey was conducted on primary caregivers of children with 22q11DS. Participants included 125 parents (114 mothers, 91.2%; average age = 44.3 years) who reported their challenges, psychological distress, and child's comorbidities of 22q11DS. Results showed that the difficulty in going to multiple medical institutions ( β = 0.181, p < 0.05) and lack of understanding by welfare staff and insufficient welfare support systems for 22q11DS ( β = 0.220–0.316, all p < 0.05) were associated with parental psychological distress, even after adjusting for child's comorbidities. In the subsample of parents whose child attended an educational institution, inadequate management in classroom and mismatch between service and users in educational settings were associated with psychological distress ( β = 0.222–0.296, all p < 0.05). This study reveals the importance of assessing not only severity of comorbidities in 22q11DS, but also the medical, welfare, and educational challenges for parental mental health.